2021
DOI: 10.3389/fphar.2021.586715
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Function, Fatty Acid Metabolism, and Body Composition in the Hyperbilirubinemic Gunn Rat

Abstract: Background: Circulating bilirubin is associated with reduced adiposity in human and animal studies. A possible explanation is provided by in vitro data that demonstrates that bilirubin inhibits mitochondrial function and decreases efficient energy production. However, it remains unclear whether hyperbilirubinemic animals have similar perturbed mitochondrial function and whether this is important for regulation of energy homeostasis.Aim: To investigate the impact of unconjugated hyperbilirubinemia on body compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 68 publications
(41 reference statements)
0
6
1
Order By: Relevance
“…However, in contrast to human studies, the hypocholesterolaemic effects appear to be sex-specific in rats with a smaller reduction observed in male Gunn rats (Wallner et al 2013). Similarly, we have observed profound sexual dimorphism in body composition, mitochondrial function and fat metabolism in hyperbilirubinaemic Gunn rats, the reason for which remains unknown (Vidimce et al 2021). However, these studies suggest that UCB and/or UGT1A1 impairment may reduce circulating cholesterol concentrations, distinct from UCB's antioxidant properties (Bulmer et al 2013).…”
Section: Introductioncontrasting
confidence: 81%
See 2 more Smart Citations
“…However, in contrast to human studies, the hypocholesterolaemic effects appear to be sex-specific in rats with a smaller reduction observed in male Gunn rats (Wallner et al 2013). Similarly, we have observed profound sexual dimorphism in body composition, mitochondrial function and fat metabolism in hyperbilirubinaemic Gunn rats, the reason for which remains unknown (Vidimce et al 2021). However, these studies suggest that UCB and/or UGT1A1 impairment may reduce circulating cholesterol concentrations, distinct from UCB's antioxidant properties (Bulmer et al 2013).…”
Section: Introductioncontrasting
confidence: 81%
“…This suggests that bilirubin regulates lipid metabolism through PPARα in male Gunn rats, but an alternative mechanism must be responsible for the changes observed in females. However, unlike studies with hyperbilirubinaemic mice that show PPARα-mediated decreases in adiposity (Hinds et al 2017), minimal changes to fat metabolism occur in male Gunn rats (Vidimce et al 2021).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Compared to wild-type mice, the body weight in the 9-months-old mice was significantly reduced in female but not in male Ugt1 −/− mice ( Figure S9A ). A similar gender-specific effect was seen in the hyper-bilirubinemic Ugt1 −/− rat caused by increased hepatic mitochondrial biogenesis in females [ 44 ]. Furthermore, the double knockout females also had a reduced body weight while their serum bilirubin levels were normal.…”
Section: Resultsmentioning
confidence: 58%
“…The capacity of bilirubin to shape a health beneficial lipid and glucose phenotype has been demonstrated in several other animal models [7,11,[47][48][49] and in vitro studies [40,50]. Numerous large prospective epidemiological studies reported that bilirubin is associated with beneficial characteristics (improved BMI, blood lipids and insulin resistance) and a reduced risk of CVD and DMT2 [9,10,14,15,[51][52][53][54].…”
Section: Discussionmentioning
confidence: 94%